Ectopic Origin of Left Coronary Ostium from Left Ventricle, with Occlusive Membrane: A Previously Unreported Anomaly, with an Embryologic Interpretation - Pirelli, Luigi (Texas Heart Institute, 2008)
Congenital atresia of the left main coronary artery, a condition in which the left main trunk is developed but has been occluded since birth, is a rare coronary anomaly. Herein, we describe this anomaly's association with a subannular location of an obliterated left main ostium in a patient with a bicuspid aortic valve and severe aortic stenosis. The patient underwent successful surgery. We discuss the embryologic implications of congenital atresia of the left main coronary artery, in view of the exceptional anatomic features of this condition. To our knowledge, this is the 1st report of a left coronary artery that was found to arise from the left ventricle.